INNOVATIVE ACTIVITY OF THE MANAGER AS A CONDITION FOR ENSURING THE EFFECTIVE ACTIVITY OF THE EDUCATIONAL INSTITUTION - Стеценко, Надія; Ткачук, Галина (Modern engineering and innovative technologies, 2022)
The work examines the problem of innovative activities of the manager as a condition for ensuring effective management and development of an educational institution. The concept of "management of innovative activity" is revealed and it is determined that